Modification of subcutaneous white adipose tissue inflammation by omega-3 fatty acids is limited in human obesity-a double blind, randomised clinical trial - Fisk, Helena L; Childs, Caroline E; Miles, Elizabeth A; Ayres, Robert; Noakes, Paul S; Paras-Chavez, Carolina; Kuda, Ondrej; Kopecký, Jan; Antoun, Elie; Lillycrop, Karen A; Calder, Philip C (EBioMedicine, 2022)
BACKGROUND: Obesity is associated with enhanced inflammation. However, investigation in human subcutaneous white adipose tissue (scWAT) is limited and the mechanisms by which inflammation occurs have not been well elucidated. Marine long chain omega-3 polyunsaturated fatty acids (LC n-3 PUFAs) have anti-inflammatory actions and may reduce scWAT inflammation. METHODS: Subcutaneous white adipose tissue (scWAT) biopsies were collected from individuals living with obesity (n=45) and normal weight individuals (n=39) prior to and following a 12-week intervention with either 3 g/day of a fish oil concentrate (providing 1.1 g eicosapentaenoic acid (EPA) + 0.8 g docosahexaenoic acid (DHA)) or 3 g/day of corn oil. ScWAT fatty acid, oxylipin, and transcriptome profiles were assessed by gas chromatography, ultra-pure liquid chromatography tandem mass spectrometry, RNA sequencing and qRT-PCR, respectively. FINDINGS: Obesity was associated with greater scWAT inflammation demonstrated by lower concentrations of specialised pro-resolving mediators (SPMs) and hydroxy-DHA metabolites and an altered transcriptome with differential expression of genes involved in LC n-3 PUFA activation, oxylipin synthesis, inflammation, and immune response. Intervention with LC n-3 PUFAs increased their respective metabolites including the SPM precursor 14-hydroxy-DHA in normal weight individuals and decreased arachidonic acid derived metabolites and expression of genes involved in immune and inflammatory response with a greater effect in normal weight individuals. INTERPRETATION: Downregulated expression of genes responsible for fatty acid activation and metabolism may contribute to an inflammatory oxylipin profile and limit the effects of LC n-3 PUFAs in obesity. There may be a need for personalised LC n-3 PUFA supplementation based on obesity status. FUNDING: European Commission Seventh Framework Programme (Grant Number 244995) and Czech Academy of Sciences (Lumina quaeruntur LQ200111901).
Keywords: Adipose tissue; Fatty Acids, Omega-3; mastné kyseliny; zánět; Adipose Tissue, White; Immune system; Fatty Acids; kyseliny dokosahexaenové; Dietary Supplements; Obesity; lidé; potravní doplňky; Lipids; Inflammation; LC n-3 PUFA; omega-3 mastné kyseliny; obezita; bílá tuková tkáň; Docosahexaenoic Acids; Humans